Chemopreventive Effects of Licorice and Its Components - Bode, Ann M. (Curr Pharmacol Rep, 2015)
Cancer is still a major health issue worldwide and identifying novel but safe compounds for prevention and treatment is a high priority. Licorice (Glycyrrhiza) is a perennial plant that is cultivated in many countries and has been reported to exert antioxidant, anti-inflammatory and anticancer effects. However, some components of licorice exert unwanted side effects and therefore identifying safer licorice components would be ideal. The anticancer activities of many of the licorice components appear to include cycle arrest, apoptosis induction, and general antioxidant effects. Commonly reported indirect protein targets important in tumorigenesis include many cell cycle-related proteins, apoptosis-associated proteins, MMP proteins, COX-2, GSK-β, Akt, NF-κB, and MAP kinases. Importantly, several licorice components were reported to directly bind to and inhibit the activities of PI3-K, MKK4, MKK7, JNK1, mTOR, and Cdk2, resulting in decreased carcinogenesis in several cell and mouse models with no obvious toxicity. This review focuses on specific components of licorice for which a direct protein target has been identified.